Biochemical Timekeeping Via Reentrant Phase Transitions. Issue 12 (11th June 2021) - Portz, Bede; Shorter, James
Graphical abstract: Highlights: Reentrant phase transitions involve a round trip between two material states. Reentrant liquid–liquid phase separation (LLPS) of proteins can be tuned by RNA. Reentrant LLPS can manifest as condensates with layered functional topologies. Reentrant LLPS may enable timekeeping via self-limiting reactions. Abstract: Appreciation for the role of liquid–liquid phase separation in the functional organization of cellular matter has exploded in recent years. More recently there has been a growing effort to understand the principles of heterotypic phase separation, the demixing of multiple proteins and nucleic acids into a single functional condensate. A phase transition is termed reentrant if it involves the transformation of a system from one state into a macroscopically similar or identical state via at least two phase transitions elicited by variation of a single parameter. Reentrant liquid–liquid phase separation can occur when the condensation of one species is tuned by another. Reentrant phase transitions have been modeled in vitro using protein and RNA mixtures. These biochemical studies reveal two features of reentrant phase separation that are likely important to functional cellular condensates: (1) the ability to generate condensates with layered functional topologies, and (2) the ability to generate condensates whose composition and duration are self-limiting to enable a form of biochemical timekeeping. We relate these biochemical studies to potential cellular examples and discuss how layered topologies and self-regulation may impact key biological processes.